A New Surgical Strategy for Infective Spondylodiscitis: Comparison Between the Combined Antero-Posterior and Posterior-Only Approaches. Issue 19 (1st October 2020) - Choi, Sung Hoon; Koo, Ja Wook; Hur, Jeong Min; Kang, Chang-Nam
Abstract : Study Design: Retrospective comparative study. Objective: To investigate the radiographic and clinical effectiveness of surgical treatment using a posterior-only approach, as compared with a combined antero-posterior approach, in patients with infective spondylodiscitis. Summary of Background Data: Spondylodiscitis is the most common infectious disease of the spine. There is currently no consensus over the surgical approach, use of bone graft, and type of instrumentation for optimal treatment of infective spondylodiscitis. Methods: Seventy-nine patients who received surgical treatment for infective spondylodiscitis were divided into a combined antero-posterior (AP) group and a posterior-only (P) group. Significant differences in pre- and postoperative radiographic and clinical characteristics between the two groups were identified, and univariate and stepwise multivariate logistic regression analyses were used to determine the factors that affected the decision for treatment approach between the two groups. Results: Preoperatively, initial height loss, wedge angle, and kyphotic angle were significantly higher in the AP group. However, estimated blood loss, operation time, and last visual analogue scale score for back pain were significantly lower in the P group. There was no difference in postoperative time to reach solid fusion. Postoperative corrected kyphotic angle was 12.8° in the AP group and 5.3° in the P group. The regional wedge angle was identified as a factor that influenced use of the combined antero-posterior approach, with a sensitivity of 60%, and specificity of 89.8% at the optimal cut-off value of 8.2°. Conclusion: Interbody fusion with long-level pedicle screws fixation through a posterior-only approach was shown to be as effective as a combined antero-posterior approach for the surgical treatment of infective spondylodiscitis. A posterior-only approach is recommended when the regional wedge angle of the collapsed vertebra is less than 8.2°. Level of Evidence: 4 Abstract : In infective spondylodiscitis, a posterior-only approach using an autogenous laminar strut bone graft is as effective for infection control, kyphosis correction, and functional outcomes as a combined antero-posterior approach. A posterior-only approach is recommended when the regional wedge angle of the collapsed vertebra is less than 8.2°.